APPLICATION OF IMMERSIVE TECHNOLOGIES IN THE MODERNIZATION OF THE TEACHER’S EDUCATIONAL MATHEMATICAL SPACE - Kovtoniuk, Mariana; Koval, Denis; Soia, Olena (Physical and Mathematical Education, 2024)
Formulation of the problem. The theoretical aspects of immersive digital technologies and the practicality of their use in the transfer of knowledge and technologies can contribute to increasing the level of competence and qualifications of the younger generation through the use of virtual reality and augmented reality, which can significantly improve the quality of education and student preparation for real life, are analyzed. It can increase student motivation to study and increase the number of students receiving higher education in science, technology, engineering, and mathematics (STEM) fields. That, in turn, can help in providing a qualified workforce and increasing the innovation potential of the state, which is an essential factor for the development of an innovative economy and is currently considered one of the critical factors of economic growth and technological renewal of production in the economy, the strategic direction of the development of the economy and the country as a whole. Materials and methods. We used several methods: a systematic review of the works of modern scientists, the monitoring of Websites on the subject of research, and one’s own pedagogical experience and methods of scientific knowledge. A student questionnaire was conducted to study the use of immersion technologies in pedagogical practice and to obtain information about the degree of familiarity of students with virtual reality. Results. The study showed that the impact of immersive technologies on the educational process and learning of university students is quite significant. Most students recognized the benefits of using the virtual educational space (82% of respondents) and interactive mathematical tools (86% of respondents). They believe this approach improves their understanding of mathematical concepts (86% of respondents) and increases motivation to study mathematics (62% of respondents). Students have also recognized the additional opportunities afforded to teachers by virtual resources. That can help improve teaching methods and create a more interactive learning environment (88% of respondents). However, it is essential to consider that not all students are equally familiar with immersive technologies; some may find them less effective than conventional learning methods. Conclusions. Implementing immersive technologies should be balanced and consider students’ individual needs. Using such technologies in higher education can improve the learning process and make mathematics more accessible and exciting for students.